Performance of 25m large mesh demersal trawl off Veraval, north west coast of India - Boopendranath, M.R., Kunjipalu, K.K., Subramania Pillai, N. and (Fishery Technology, 2021)
Performance of a 25m large mesh demersal trawl, with 150mm mesh size in the fore parts of the trawl was evaluated in comparison with one boat high opening trawl of the Bay of Bengal Programme (BOBP) with 360 meshes of 160mm mesh size and 25.6m head rope length. An 8.2% increase in catch was obtained by 25m large mesh demersal trawl. The gear is comparatively cheaper, lighter in construction and offered better horizontal spread with significantly lower towing resistance. Commercial suitability of the gear for efficient harvesting of demersal fish resources of the region is discussed.